Insulin resistance and roncomitant macro- and microvascular dysfunction in normoglycemic college-age subjects with a family history of type 2 diabetes - Townsend, Dana Komarek (Kansas State University, 2007)
The overall aims of this dissertation are to determine the incidence and magnitude of insulin resistance (IR) in a cohort of normoglycemic college-age subjects with a family history of type 2 diabetes, and to ascertain if there is early macro- and microvascular dysfunction relative to IR. Study 1 (Chapter 2) revealed a 7-fold range in IR in healthy college subjects concomitant with measures of insulin, both fasted and during an oral glucose tolerance test, but not related with any measure of plasma glucose. These results emphasize that early in the etiology of carbohydrate dysregulation, abnormalities first occur with regard to insulin sensitivity. Using brachial artery blood flow (BABF, Doppler fluxometry) and near-infrared spectroscopy (NIRS) (Chapter 3) we extended the understanding of the use of these non-invasive tools to assess forearm resting metabolic rate and to compare the parameters of both the NIRS oxy-hemoglobin signal, as a index of perfusion in the microcirculation, and BABF, as an independent measure of microvascular reactivity during post occlusive reactive hyperemia (PORH). Resting metabolic rate ranged ~ 2 fold (2.83-5.15 [Mu]MO[subscript2]/min/100g) similar to direct measures. Amplitude, but not kinetic parameters for NIRS variables correlated with comparable parameters for BABF, providing evidence for the possible utility of NIRS in examining microvascular reactivity. In study 3 (Chapter 4), utilizing our extended understanding of hemodynamics garnered from the results of study 2, we assessed the influence of IR on macro- and microvascular reactivity. We observed that i) the magnitude of IR was significantly correlated with attenuation of endothelium-dependent vasodilation of the brachial artery (P< .01) indicating the possibility of a reduced nitric oxide bioavailability and an enhanced atherogenic milieu. Additionally we found ii) BABF at rest and during reactive hyperemia to be strongly correlated with conductance (reduced downstream resistance—an indicator of microvascular control abnormalities) independent of forearm metabolic rate, and iii) parameters of BABF (microvascular response) were also strongly correlated with brachial artery vasoreactivity (macrovascular response). In conclusion, this body of work furthers our insight into the need for earlier identification of "disease" earlier in the progression to type 2 diabetes, and provides direction for future investigations into prevention / intervention to improve microvessel functionality and to slow the atherosclerotic process in larger vessels.
Keywords: insulin resistance; endothelial dysfunction; microvascular dysfunction; normoglycemia; college-age; physiology; Biology, Animal Physiology (0433)